2021
DOI: 10.3390/ma14216401
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Carbon Fiber Reinforced Polymers Recycling: A Review of Recycling Methods and Reuse of Carbon Fibers

Abstract: The rapid increase in the application of carbon fiber reinforced polymer (CFRP) composite materials represents a challenge to waste recycling. The circular economy approach coupled with the possibility of recovering carbon fibers from CFRP waste with similar properties to virgin carbon fibers at a much lower cost and with lower energy consumption motivate the study of CFRP recycling. Mechanical recycling methods allow the obtention of chopped composite materials, while both thermal and chemical recycling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 98 publications
(105 reference statements)
1
34
0
Order By: Relevance
“…As for the mechanical properties of heat-treated fibers, they retain 90-95% of the initial ones at optimized conditions of pyrolysis and oxidation [25]. Based on the literature data and preliminary experiments (Figure 4), it is shown that annealing in the air, in contrast to pyrolysis in an inert atmosphere, provides the separation of fibers with a clean surface.…”
Section: -2-pyrolysis or Calcination?mentioning
confidence: 93%
See 4 more Smart Citations
“…As for the mechanical properties of heat-treated fibers, they retain 90-95% of the initial ones at optimized conditions of pyrolysis and oxidation [25]. Based on the literature data and preliminary experiments (Figure 4), it is shown that annealing in the air, in contrast to pyrolysis in an inert atmosphere, provides the separation of fibers with a clean surface.…”
Section: -2-pyrolysis or Calcination?mentioning
confidence: 93%
“…Depending on the atmosphere and duration [12], PCM waste pyrolysis at 400-600°C preserves the tensile strength of fibers from 50 to 95% of the initial one. However, the surface of fibers is often covered with residual pyrocarbon and requires additional calcination in air at the same temperature [25,45]. However, the surface of the fibers is often covered with pyrocarbon residues and requires additional calcination in air at the same temperature [25,45].…”
Section: -2-pyrolysis or Calcination?mentioning
confidence: 99%
See 3 more Smart Citations